Multi-objective scheduling in PCB assembly manufacturing : discrete event simulation approach - Zuo, Jie (2014)
In PCB Assembly manufacturing environment, there are usually three objectives to achieve – minimizing setup cost, minimizing average cycle time, and minimizing job lateness. With the re-entrant trait of PCB Assembly system, scheduling job release is a complicated but crucial problem which plays an important role in improving the whole factory performance, maximizing factory production capability, minimizing waste and maximizing revenue. How to schedule jobs with dynamic queue to achieve the three objectives is where we focus on.